The FOODia-Net Protocol. (30th September 2020) - Graps, E A; Giuliani, R; Graffigna, G; Bosio, C; Damiani, G; Francesconi, P; Chiaramonte, F; Lattanzio, F; Franchetti, M; Castelli, N
Abstract: The increasing of chronic diseases represents a worldwide issue and conceiving effective operating models of preventive care looks mandatory to satisfy new health and social needs. It is known from Evidence-Based Medicine that to combine a multidisciplinary/multiprofessional care approach with the promotion of patients' health literacy and correct lifestyle can improve chronic diseases management at global level. Five Italian Regions are currently collaborating in the framework of the National Centre for Diseases Prevention and Control Research Call funded by the Italian Ministry of Health. The Project ultimate goal is the implementation of an innovative skill-mix-change operating Protocol aimed to promote patient engagement and food literacy about diabetes and its complications. To pursuit this objective and to conduct the Project dissemination activities, the creation of a dedicated web-based platform is scheduled. The assessment of the effectiveness and sustainability of the whole Project is foreseen. A non-systematic review of available publications about existing skill-mix-change approaches designed to promote food literacy and patient engagement has been performed and a cross-sectional study to investigate food literacy of diabetic patients has been drawn up. It was approved by Local Review Board in February 2020. Meanwhile a requirements audit among Partners has been carried out to outline the ICT framework for commissioning the creation of the web-based platform to support dissemination activities. The Project is ongoing. With the aim to preliminary map existing educational initiatives on diabetes an initial scenario analysis shows that: counselling initiatives are performed in 89% of GPs groups; patient engagement initiatives in 52% and training initiatives in 58%. Training initiatives for professionals take place in 27% of clinics; at least 1 initiative, on diabetes prevention or food literacy promotion, is carried out in each of the 9 Associations registered.